0028 Network Analysis of Adipokines in Sleep Disorders and Metabolic Dysregulation. (25th May 2022) - Wei, Zhikui; Chen, You; Upender, Raghu
Abstract: Introduction: Adipokines are a growing group of secreted proteins that play important roles in metabolism. Accumulating evidence suggests that adipokines may mediate the close association between sleep disturbance and metabolic derangements. Due to the extensive crosstalk between adipokines and metabolic pathways, an integrated approach is required to better understand the significance of adipokines in sleep disorders and associated metabolic dysregulation. In the current study, we employed network analysis, a set of concepts and methods derived from graph theory, to obtain novel insights into the roles of adipokines in sleep disorders and associated metabolic dysregulation. Methods: A network of six adipokines and their molecular targets is constructed based on current understanding of their roles in sleep and metabolic disorders using an adjacency matrix. The network is then visualized and analyzed using an open source platform Gephi to derive network-level metrics, including degree and centrality measures. These metrics are used to explore the relationship between sleep disturbance and associated metabolic dysregulation in several disease processes. Results: 94 nodes and 264 edges were identified in the network, representing regulatory factors, adipokines, molecular pathways, and disease processes. Two adipokines, leptin and adiponectin, were found to have higher degrees than other adipokines, indicating their central roles in connecting sleep disturbance to metabolic dysregulations. Among the regulatory factors, obesity and obstructive sleep apnea were found to be major drivers for the sleep associated metabolic dysregulation based on their higher degrees. The important pathways adipokines act on in the network included insulin signaling, inflammation, food intake, and energy expenditure. The main disease processes adipokines act on included cardiovascular, reproductive, and autoimmune diseases. Leptin, AMPK, and fatty acid oxidation were found to have global influence in the network based on their high betweenness. Conclusion: Adipokines are important players in the metabolic dysregulations associated with sleep disturbance. Adipokines such as leptin and adiponectin act on diverse metabolic pathways in response to sleep disturbance, obesity, insulin resistance, and inflammation.They play important roles in cardiovascular, reproductive, and autoimmune diseases. Adipokines and their targets, such as leptin, AMPK, and fatty acid oxidation are likely important interventional/pharmaceutical targets for these disease processes. Support (If Any): none